Preservatives and Preservation Approaches in Beverages - Grumezescu, Alexandru Mihai; Holban, Alina Maria (Science of beverages, 2019)
Preservatives for the Beverage Industry, Volume Fifteen, a new release in The Science of Beverages series, is a valuable resource that discusses preservatives and their impact in the beverage industry, including potential health impacts. The book takes a broad, multidisciplinary approach to explore both conventional and novel approaches of the types and uses of preservatives. The latest applications and techniques to reduce the use of non-natural or health-threatening preservation elements are also covered. This is a must-have reference for anyone who needs to increase their technical-scientific knowledge in this field. --